A Case Study of Novice Bilingual Education Teachers Conducting Action Research and Diffusing Teaching Innovations. (October 2021) - Acosta, Sandra T.; Chen, Xuewei; Goltz, Heather; Goodson, Patricia; Padrón, Yolanda
This case study examined action research conducted by bilingual education teachers in urban schools as a tool for progressing from novice-to-expert teachers. We described a longitudinal study across four cohorts of first-year bilingual education teachers as action researchers ( n = 9). The study investigated the following: (a) how school leaders and colleagues responded to knowledge (innovations) generated through practitioner inquiry and (b) teacher–researchers' perceptions about the process and outcomes of sharing their research findings with school leaders and colleagues. Findings clustered around two patterns: feelings of teacher self-efficacy and workplace isolation. Principals perceived innovations as human capital, not social capital.